Microglia Polarization in Alzheimer’s Disease: Mechanisms and a Potential Therapeutic Target - Wang, Qinqin; Yao, Hongmei; Liu, Wenyan; Ya, Bailiu; Cheng, Hongju; Xing, Zhenkai; Wu, Yili (Frontiers in Aging Neuroscience, 2021)
Neuroinflammation regulated by microglia is one of the important factors involved in the pathogenesis of Alzheimer’s disease (AD). Activated microglia exhibited phenotypes termed as M1 and M2 phenotypes separately. M1 microglia contribute to the development of inflammation via upregulating pro-inflammatory cytokines, while M2 microglia exert anti-inflammation effects through enhancing the expression of anti-inflammation factors. Moreover, M1 and M2 microglia could be mutually transformed under various conditions. Both M1 and M2 microglia has been implicated in AD. β-amyloid (Aβ) and hyperphosphorylated tau are wo major components of AD pathological hallmarks, neuritic plaques and neurofibrillary tangles. Both Aβ and hyperphosphorylated tau were involved in microglial activation and subsequent inflammation, which further contribute to neuronal and synaptic loss in AD. In this review, we summarize the roles of M1 and M2 microglia in AD and underlying mechanisms, which will provide an insight into the role of microglia in the pathogenesis of AD and highlight the therapeutic potential of modulating microglia.